.NET Standard 2.0 Cookbook : Develop high quality, fast and portable applications by leveraging the power of .NET Standard Library. - Ismail, Fiqri (Packt Publishing, 2018)
.NET Standard is a standard that represents a set of APIs that all .NET platforms have to implement, making it easier for developers to access and use one common library for their development needs. If you want to get the best of the .NET framework using the Standard Libraries and program in a better way, then this book is for you.